The Photocatalytic Inactivation Effect of Fe-Doped TiO2 Nanocomposites on Leukemic HL60 Cells-Based Photodynamic Therapy - Kangqiang Huang; Li Chen; Meixiang Liao; Jianwen Xiong (International Journal of Photoenergy)
The Fe-doped TiO2 nanocomposites synthesized by a deposition-precipitation method were characterized by X-ray diffraction (XRD), transmission electron microscope (TEM), X-ray photoelectron spectroscopy (XPS), and UV-vis adsorption spectra and then were taken as a new “photosensitizer” for photodynamic therapy (PDT). The photocatalytic inactivation of Fe-doped TiO2 on Leukemic HL60 cells was investigated using PDT reaction chamber based on LED light source, and the viability of HL60 cells was examined by Cell Counting Kit-8 (CCK-8) assay. The experimental results showed that the growth of leukemic HL60 cells was significantly inhibited by adding TiO2 nanoparticles, and the inactivation efficiency could be effectively enhanced by the surface modification of TiO2 nanoparticles with Fe doping. Furthermore, the optimized conditions were achieved at 5 wt% Fe/TiO2 at a final concentration of 200 μg/mL, in which up to 82.5% PDT efficiency for the HL60 cells can be obtained under the irradiation of 403 nm light (the power density is 5 mW/cm2) within 60 minutes.